2003
DOI: 10.1124/jpet.102.048132
|View full text |Cite
|
Sign up to set email alerts
|

AGI-1067: A Multifunctional Phenolic Antioxidant, Lipid Modulator, Anti-Inflammatory and Antiatherosclerotic Agent

Abstract: To explore the therapeutic efficacy and potential mechanisms of action of a new class of antiatherosclerotic drugs, AGI-1067 [mono[4-[[1-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]thio]-1-methylethyl]thio]-2,6-bis(1,1-dimethylethyl)phenyl] ester] (butanedioc acid) was tested in several animal models of atherosclerosis. AGI-1067, a novel phenolic antioxidant, was well tolerated in a 1-year study in hypercholesterolemic cynomolgus monkeys. It lowered low-density lipoprotein cholesterol (LDLc) by 41 and 90% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 42 publications
5
57
0
Order By: Relevance
“…Doses of succinobucol up to 150 mg/kg had no effect on MAP or HR in anaesthetized rats. These doses are in line with previous in vivo studies in animals [2], albeit that treatment was chronic in this study. A previous study reported raised systolic blood pressure in humans taking succinobucol chronically [5] but we observed no effect after acute administration in rats, suggesting that effects on blood pressure develop over time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Doses of succinobucol up to 150 mg/kg had no effect on MAP or HR in anaesthetized rats. These doses are in line with previous in vivo studies in animals [2], albeit that treatment was chronic in this study. A previous study reported raised systolic blood pressure in humans taking succinobucol chronically [5] but we observed no effect after acute administration in rats, suggesting that effects on blood pressure develop over time.…”
Section: Discussionsupporting
confidence: 81%
“…Succinobucol [mono [4-[[1-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]thio]-1-methylethyl]thio]-2,6-bis(1,1-dimethylethyl) phenyl] ester] (butanedioc acid) is a phenolic antioxidant derivative of probucol, which has consistently demonstrated improved pharmacokinetics, antiproliferative, and anti-inflammatory effects compared with probucol [1][2][3]. Succinobucol inhibits cytokine release by monocytes and expression of proinflammatory cell adhesion molecules by endothelial cells (ECs) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The drug (AGI-1067) had been shown to inhibit atherogenesis in animal models (42), but it failed to show any decrease in its primary composite end point of cardiovascular death, resuscitated cardiac arrest, nonfatal myocardial infarction, nonfatal stroke, hospitalization for unstable angina, or coronary revascularization above that seen with statin therapy alone (43). Data to evaluate antioxidant effect were not presented.…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…Furthermore, these peptides do not appear to significantly alter plasma lipid parameters. In this respect, synthetic small molecule ACAT inhibitors have also been shown to have this effect without reducing plasma cholesterol levels (26)(27)(28). This is not surprising, because the administration of these peptides, as liposomes, would target M primarily and not the total body synthesis of cholesterol.…”
Section: Discussionmentioning
confidence: 99%